Understanding the Treaty of Lisbon - Clive H. Church; David Phinnemore (Romanian Journal of European Affairs, 2010)
The entry into force of the Treaty of Lisbon comes at a time of continuing lack of agreement about its significance thus justifying a new and less polarized assessment. The article looks at previous assessments, including those that see the Treaty as a major breakthrough for efficiency backed by a new political dynamic and as the unnecessary and undemocratic imposition of a superstate and noxious policies. The article assesses the status, structure and style of the treaty and its contents, highlighting its provisions on values and rights, powers and policies, institutional changes, democratization and enhanced external activity. These, like assessments of the treaty, are often contradictory and point to the fact that Lisbon was yet another compromise document and not a master blueprint. Hence the resulting Union is likely to be a messy hybrid, being legalistic, lacking a single power centre, uncertainly democratic and enshrining more constructive ambiguity.